BIG DATA AND TELEVISION BROADCASTING. A CRITICAL REFLECTION ON BIG DATA’S SURGE TO BECOME A NEW TECHNO-ECONOMIC PARADIGM AND ITS IMPACTS ON THE CONCEPT OF THE «ADDRESSABLE AUDIENCE» - Paul Clemens MURSCHETZ,Daniela SCHLÜTZ (Fonseca, Journal of Communication, 2023)
The paper explores how big data creates challenges and opportunities to enhance value relationships between TV broadcasters, audiences and advertisers in digital television broadcasting. It finds that research into big data requires much closer attention to critical issues in the social and cultural sciences – with a focus on media and communication studies and its subfield media management – to inspire our understanding that big data would perfectly fit the dominant «techno-economic paradigm», a meta-narrative for a substantial technological revolution that has the power to bring about a transformation across the board in ways that when new technologies diffuse, they multiply their impact across the economy and eventually modifies the socio-institutional structures.